Implications of Financial Literacy, Illusion of Control and Overconfidence through Emotional Maturity towards People's Investment Decisions during a Pandemic - Ishak, Parmin; Sholehah, Nur Lazimatul Hilma (CV. Rayyan Dwi Bharata, 2023)
This study aims to: (1) Find out how much influence financial literacy has on people's emotional maturity during a pandemic; (2) Knowing how much influence the illusion of control has on people's emotional maturity during the pandemic; (3) Knowing how much influence overconfidence has on people's emotional maturity during the pandemic; (4) Knowing how much financial literacy directly and indirectly affects people's investment decisions during the pandemic; (5) Knowing how much influence the illusion of control has directly and indirectly on people's investment decisions during the pandemic; (6) Knowing how much influence overconfidence directly and indirectly has on people's investment decisions during the pandemic; (7) Knowing how much emotional maturity affects people's investment decisions during the pandemic. This type of research is quantitative research. The object of this study is people in Tilamuta District who are involved in investment. The sampling technique in this study used the cluster sampling method. Data collection was carried out through a survey method using a questionnaire that was distributed directly to people in mohungo village who were involved in investment activities. The results of this study show that (1) Financial literacy has an insignificant negative effect on emotional maturity in the mohungo village community of Tilamuta District, (2) Illusion of control has an insignificant positive effect on emotional maturity in the mohungo village community of Tilamuta District, (3) Overconfidence has an insignificant positive effect on emotional maturity in the mohungo village community of Tilamuta District, (4) Financial literacy indirectly affects the community of Mohungo village, Tilamuta District, (4) Financial literacy indirectly affects positive and significant towards investment decisions through emotional maturity in the people of mohungo village, Tilamuta District, (5) Illusion of control indirectly has an insignificant negative effect on investment decisions through the emotional maturity of the community in mohungo village, Tilamuta District, (6) Overconfidence indirectly has a negative and significant effect on investment decisions through the emotional maturity of the community in mohungo village, Tilamuta District, (7) Emotional maturity has a negative and significant effect on investment decisions in the mohungo village community of Tilamuta District. With mandatory outputs in the form of accredited national journals